Preliminary study on the fabrication and characterization of pressure retarded osmosis flat-sheet membranes - Lim, Jun Yuan (2014)
The rapid depletion of natural fuel sources and the ever-growing need for water and energy has raised the concerns to find a sustainable supply for these resources. As a result, Pressure Retarded Osmosis (PRO) process became an attractive option for researchers to work on. Despite this technology being available, development of PRO membranes is needed to utilize the power production. As an osmotically membrane process, PRO process is affected by internal concentration polarization problems, which results in lower effective osmotic pressure. This problem can be mitigated by producing a high porous substrate, however this would reduce the mechanical strength of membrane. In PRO applications, high mechanical strength is required due to hydraulic pressure on the draw side of the membrane. Hence, an efficient membrane must be developed for future application of PRO technology. PRO membrane recipes with different substrates were proposed for this investigation and their performance was evaluated experimentally.